2011
DOI: 10.1074/jbc.m111.264572
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Poly(A)-binding Protein Pab1p in PUF Protein-mediated Repression

Abstract: PUF proteins regulate translation and mRNA stability throughout eukaryotes. Using a cell-free translation assay, we examined the mechanisms of translational repression of PUF proteins in the budding yeast Saccharomyces cerevisiae. We demonstrate that the poly(A)-binding protein Pab1p is required for PUF-mediated translational repression for two distantly related PUF proteins: S. cerevisiae Puf5p and Caenorhabditis elegans FBF-2. Pab1p interacts with oligo(A) tracts in the HO 3-UTR, a target of Puf5p, to dramat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 55 publications
(78 reference statements)
1
14
0
Order By: Relevance
“…We note that our attempts to detect association of eIF4G with Pum RBD have been unsuccessful. Supporting this model, Chritton and Wickens showed that the Pab1-eIF4G interaction is required for repression by yeast Puf5 in vitro (Chritton and Wickens 2011). As a result, Pumilio would disrupt the "closed loop" contacts between 5…”
Section: Pumilio Represses By Targeting Pabpmentioning
confidence: 83%
See 2 more Smart Citations
“…We note that our attempts to detect association of eIF4G with Pum RBD have been unsuccessful. Supporting this model, Chritton and Wickens showed that the Pab1-eIF4G interaction is required for repression by yeast Puf5 in vitro (Chritton and Wickens 2011). As a result, Pumilio would disrupt the "closed loop" contacts between 5…”
Section: Pumilio Represses By Targeting Pabpmentioning
confidence: 83%
“…Using a translationally active yeast extract, the pAbp ortholog, Pab1p, was shown to participate in translational inhibition by the RBD of yeast Puf5 (Chritton and Wickens 2011). In this same yeast extract, the RBD of C. elegans FBF also inhibited translation in a Pab1p-dependent manner (Chritton and Wickens 2011). In addition, pAbp colocalizes with PUFs in ribonucleoprotein granules in rat neurons (Vessey et al 2010).…”
Section: Pumilio Represses By Targeting Pabpmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the proximity of the GC-rich stem-loop to the poly(A) tail inhibits cooperative binding of Pab1 to the poly(A) tail and neighboring sequences. Because Pab1 can interact with sequences upstream of cleavage and polyadenylation sites (Simón and Séraphin, 2007; Chritton and Wickens, 2011), any reduction in single-stranded character at the 3′ ends of isoforms and/or poly(A) tails might result in reduced Pab1 binding. It is also possible that the GC-rich elements may be forming higher-order structures such as triple helices that shield the poly(A) tail (Mitton-Fry et al, 2010; Brown et al, 2012; Tycowski et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, PABPs are involved in both general mRNA metabolism, such as control of mRNA half-life and nonsense mediated decay (NMD) [3], [4], and in mRNA specific functions [5]. The latter includes the regulation of translation by binding to A-rich stretches in 5′ UTRs [6] or 3′ UTRs [7], [8], [9], including the 5′ UTR of its own mRNAs [10], [11], [12], [13], an involvement in miRNA induced silencing by binding to the miRISC complex [14], [15] and contributing to nuclear mRNA processing [16]. Similarly, eIF4E proteins can repress translation of individual mRNAs.…”
Section: Introductionmentioning
confidence: 99%